Reducing computational time of cohesionless discrete simulations based on particle clusters. Issue 2 (18th April 2017) - Oldal, Istvan; Safranyik, Ferenc; Keppler, Istvan
Abstract : Purpose: The purpose of this study is the reduction of computational time demand of discrete element based modeling. Design/methodology/approach: The methodology is the systematic changing of particle size and micromechanical parameters to reduce computational time requirements. Findings: In some cases, the computational demand of discrete simulations can be reduced to about 95 per cent. Originality/value: Based on the results and demonstrated methodology, the enormous computational time demand of discrete element-based modeling can be reduced significantly.